Fish Assemblages in Iraqi Marine Waters, North West The Arabian Gulf - Al-Shamary, Ahmed CH.; Younis, Kadhim H.; Yuosif, Usama H. (Iraqi Journal of Science, 2021)
The composition of fish assemblages in Iraqi marine water was assessed. 91 species belonging to 71 genes and 47 families of Osteichthyes and 13 species of Conderchthyes were collected during the study period from January to December 2018, using trawl net fishing. Three stations were selected, where two new species (Siganus javus and Gobiopsis sp.) and reclassification of Torpedo panthera where identified and two species of freshwater fish (Oreochromis niloticus and Oreochromis aureus) were first recorded in marine waters. The highest numbers of species were 32 and 42 for the first and second stations, respectively, recorded in October , while 55 species were recorded in the third station during August. Leiognathus bindus was the dominant species in the first and second stations, while Ilisha compressa dominated the third station. Carangidae and Sciaenidae were the dominant families in number of species (7 and 5, respectively), whereas 4 species were recorded for Clupeidae, Sparidae, Mugilidae and Gobidiae.